Diagnosis and Management of Benign Liver Tumors - Chiche, Laurence; Adam, Jean-Philippe (Seminars in Liver Disease, 2013)
The widespread use of imaging modalities and the continuous improvement in their sensitivity have lead to an increasing number of incidental findings of focal liver masses, either solitary or multiple. Most of these so-called incidentalomas are benign and are discovered in healthy, asymptomatic patients. The main issue is to ensure the proper diagnosis, so that clear management recommendations can be provided. Surgery is rarely indicated in these circumstances. Infrequently, benign liver tumors are diagnosed because of symptoms or complications, and require urgent management including surgery as a major role in the cure. Due to better understanding of the clinical and pathological features of benign liver tumors, the increased accuracy of imaging tools, and improvement in surgical techniques (including laparoscopy), the management of these lesions has evolved. Here the clinical and biological features of the most common solid and cystic benign liver tumors are reviewed, and the key points of management focusing on the role of surgery, preventive or diagnostic, are addressed.
Keywords: benign liver tumor; hemangioma; focal nodular hyperplasia; hepatocellular adenoma; adenomatosis